An inverse method for distributed dynamic load identification of structures with interval uncertainties. (May 2019) - Wang, Lei; Liu, Yaru; Liu, Yisi
Highlights: A time-domain based method for distributed dynamic load identification considering unknown-but-bounded uncertainties in structural systems. The reconstruction method is investigated to acquire the envelope interval of the identified load by combining uncertainty propagation analysis and the inverse problems in dynamics. The distributed dynamic load acting on continuous structures may be spatially approximated by Chebyshev orthogonal polynomial at each sampling time. Abstract: A time-domain based method for distributed dynamic load identification is proposed in this study considering unknown-but-bounded uncertainties in structural systems. The spatiotemporal dynamic load is further approximated by Chebyshev orthogonal polynomial in time history. Thus, the problem of distributed load reconstruction may be converted into the issue of polynomial coefficient calculation at each sampling time by utilizing a series of dynamic analysis. In accordance with the practical engineering, the acceleration response is used as the system input. In terms of the uncertainty quantification problems, the interval analysis method based on Taylor expansion (IAMBTE) is systematically developed to accomplish the envelope interval of identified load. To facilitate the analysis, two kinds of load are required to be identified, among which the nominal value of the identified load may be straightforwardly achieved through the inverse system, whereas the interval boundaries should be settled by the interval propagation analysis. Eventually, two numerical examples are investigated to demonstrate the efficiency and precision of the developed methodology.